PENGARUH CAR, NPL, BOPO, NIM, LDR TERHADAP ROA PADA PT BANK TABUNGAN NEGARA,TBK PERIODE TAHUN 2008-2020 - Rahmi, Palupi Permata; Herlina, Listri (Jurnal Ekonomi : Journal of Economic, 2021)
AbstractThis study aims to analyze the effect of Capital Adequacy Ratio (CAR), Non Performing Loan (NPL), Operational Costs on Operating Income (BOPO), Net Interest Margin (NIM) and and Loan to Deposit Ratio (LDR) on Return on Assets (ROA). ) at PT Bank Tabungan Negara, Tbk for the period 2008-2020. The sample used in this study is PT Bank Tabungan Negara, Tbk for the period 2008-2020. This research uses descriptive and quantitative approaches. The results showed that partially CAR, BOPO and LDR had no significant effect on ROA at PT Bank Tabungan Negara, Tbk for the Period of 2008-2020. Meanwhile, NPL and NIM partially have a significant effect on ROA. Simultaneously, CAR, NPL, OEOI, NIM and LDR have a significant effect on ROA at PT Bank Tabungan Negara, Tbk for the Period of 2008-2020. Keywords: CAR, NPL, BOPO, NIM, LDR, and ROA